2021
DOI: 10.1108/ilt-07-2021-0282
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of leakage characteristics for bent-axis piston pump based on elastohydrodynamic deformation

Abstract: Purpose This paper aims to revel the leakage characteristics of the bent-axis piston pump considering elastohydrodynamic deformation via a dynamic leakage model. Design/methodology/approach A dynamic leakage model of bent-axis piston pump based on elastohydrodynamic lubrication theory is proposed, which is used to present the leakage characteristics of bent-axis piston pump. The model is composed of three parts. First, the dynamic gap in the piston ring-cylinder bore interface (PRCB) is described via the ela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The experimental results in Table 2 show that the pump's total leakage increases with the rotational speed. One may consider that the large measured leakage at high rotational speed results from the centrifugal flow that increases with the rotational speed, as shown in equations (20) and (28). However, at the same time, these two equations indicate that the centrifugal flow actually contributes little to the leakage flow.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental results in Table 2 show that the pump's total leakage increases with the rotational speed. One may consider that the large measured leakage at high rotational speed results from the centrifugal flow that increases with the rotational speed, as shown in equations (20) and (28). However, at the same time, these two equations indicate that the centrifugal flow actually contributes little to the leakage flow.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al 19 developed a nonlinear theoretical model based on Reynolds equation to predict the leakage of piston/cylinder block interface. Qing et al 20 compared the contributions of Poiseuille and Couette flows to the leakage of piston/cylinder block interface. Nie et al 21 established a fluid–structure interaction model for the piston/cylinder block interface, by which they found that the piston bush deformation increased the interface leakage due to increased gap height.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, he studied the influence of the material and structure of the valve plate on the thickness and shape of the oil film 13. Qing et al proposed a dynamic leakage model of bent-axis piston pump based on elastohydrodynamic lubrication theory, which is used to present the leakage characteristics of bent-axis piston pump 14. Deng et al analyzed the hydrodynamic lubrication characteristics of the external return spherical bearing pair of an axial piston pump/motor 15.…”
Section: Introductionmentioning
confidence: 99%